Assessment of the cytotoxic activity of humates produced by “Shubarkol Komir” JSC - Zhumina, A.; Orazbay, A.; Martynova, Y.; Abyurov, A.; Safronova, I.; Kulandin, M.; Jexembayev, D. (Fundamental and Experimental Biology, 2026)
The development of new humic preparations from locally available raw materials is important for advancing the domestic industry of the Republic of Kazakhstan. In Central Kazakhstan, humic preparations such as potassium humate and sodium humate have been developed by “Shubarkol Komir” JSC based on weathered coal. To confirm their applicability, studies assessing their biological activity and safety are required. The purpose of this study is to evaluate the cytotoxic activity of potassium humate and a mixture of potassium humate and humate in different dilutions. The study materials included humates produced by “Shubarkol Komir” JSC, which were compared with a commercial preparation, ECO humate, using tests on Saccharomyces cerevisiae cells and Artemia salina nauplii. The test results showed that high concentrations of humic preparations (4 %) had an inhibitory effect on the foaming ability of yeast, which was lower than that of the comparison drug nystatin. Concentrations from 0.5 to 0.005 % did not inhibit Saccharomyces cerevisiae and activated the foaming ability. The results of the second experimental series demonstrated that both the humates produced by “Shubarkol Komir” JSC and the reference preparation were non-cytotoxic to Artemia salina larvae at all tested concentrations (0.5–0.005%), indicating their safety. Thus, the obtained data confirm the safety of using potassium humate and a mixture of potassium humate and sodium humate produced by “Shubarkol Komir” JSC in agriculture.